Sleuthing the Bible: clues that unlock the mysteries of the text - Kaltner, John (William B. Eerdmans Publishing Company, 2019)
The clue of the intrusive narrator -- The clue of the physical description -- The clue of the etiology -- The clue of the weird social custom -- The clue of the inconsistency -- The clue of the doublet -- The clue of the echo -- The clue of the repeated pattern -- The clue of the broken pattern -- The clue of the telegraphed information -- The clue of the name -- The clue of the anachronism -- The clue of the hidden meaning -- The clue of the messy manuscript -- The clue of the perspectival bias.